Micro- and mesoporous carbide-derived carbon-selenium cathodes for high-performance lithium selenium batteries - Lee, Jung Tae; Kim, Hyea; Oschatz, Martin; Lee, Dong-Chan; Wu, Feixiang; Lin, Huan-Ting; Zdyrko, Bogdan; Cho, Won Il; Kaskel, Stefan; Yushin, Gleb (Advanced Energy Materials, 2015)
Nanocomposites of selenium (Se) and ordered mesoporous silicon carbide-derived carbon (OM-SiC-CDC) are prepared for the first time and studied as cathodes for lithium-selenium (Li-Se) batteries. The higher concentration of Li salt in the electrolytes greatly improves Se utilization and cell cycle stability. Se-CDC shows significantly better performance characteristics than Se-activated carbon nanocomposites with similar physical properties. Se-CDC also exhibits better rate performance and cycle stability compared to similarly produced sulfur (S)-CDC for Li/S batteries.
CRIS-Team Scopus Importer:2023-03-20